2018
DOI: 10.1016/j.npep.2018.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced changes in neurotrophic factors and markers of blood-brain barrier permeability are moderated by weight status in multiple sclerosis

Abstract: Blood-brain barrier (BBB) and neurotrophic factors seemingly have an important role in multiple sclerosis pathology. Physical activity may influence blood-brain barrier function and levels of neurotrophic factors, and such effects might be moderated by body weight status. This study investigated the effect of exercise training on markers of blood-brain barrier permeability and neurotrophic factors as a function of weight status in multiple sclerosis patients. Sixty three persons with relapsing remitting multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 40 publications
4
54
1
1
Order By: Relevance
“…Three studies focused on BBB function markers in pwMS (Table ). Studies used peripheral circulation markers including matrix metallopeptidase (MMP)‐9 , MMP‐2 , s100 calcium‐binding protein B and neuron‐specific enolase . Results of BBB markers studies revealed a positive effect of exercise, particularly where s100 calcium‐binding protein B was investigated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies focused on BBB function markers in pwMS (Table ). Studies used peripheral circulation markers including matrix metallopeptidase (MMP)‐9 , MMP‐2 , s100 calcium‐binding protein B and neuron‐specific enolase . Results of BBB markers studies revealed a positive effect of exercise, particularly where s100 calcium‐binding protein B was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Results of BBB markers studies revealed a positive effect of exercise, particularly where s100 calcium‐binding protein B was investigated. Nine studies focused on neurotrophic factors (Table ) including brain‐derived neurotrophic factor (BDNF) , nerve growth factor , neurotrophin‐4 (one study), platelet‐derived growth factor and ciliary neurotrophic factor in pwMS. Among eight studies that investigated the effects of exercise training on BDNF, four studies reported a significant increase (see Appendix S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of older women, exercise and exercise combined with taurine supplementation (a common amino acid in the body that declines with age) led to reduced peripheral inflammation and increased integrity of the BBB as measured by both S100β and NSE (Chupel et al, ). Similarly, exercise led to decreases in S100β (though no changes in NSE) among normal weight patients with MS (Mokhtarzade et al, ).…”
Section: Healthy Behaviors and The Neuro‐immune Networkmentioning
confidence: 93%